Neurotoxin Botulinum Inserts Apoptotic Effects on Certain Cancer Cell Lines Via Neural Niche of Tumors: A Molecular Study - Farhadi, Mona; Jameie, Melikasadat; Derakhshanmehr, Bahareh; Tahmasebi, Moghadam; Soleimani, Maryam; Jameie, Seyed Behnamedin (International Clinical Neuroscience Journal, 2020)
Background: Background: Botulinum toxin A (BtxA) is a powerful neurotoxin reported to be effective as a cancer adjuvant therapy with fewer side effects. Previously we showed the apoptotic effects of BtxA on the GBM cell line (U87-MG). In order to confirm the positive neurotoxicity of BtxA on other cancer cell lines, including SK-OV-3, CHO, MCF-7, and PC-3, the present research has designed. Methods: The cell lines prepared, cultured, and exposed to different concentrations of BtxA for 24 and 48 hours. Using MTT, Annexin V/PI assays and western blotting, cell viability, and apoptosis studied. Results: Our results showed that different BtxA Botox concentrations led to significant cell death in each cell line in a dose-dependent manner (P < 0.001) but did not for PC-3 cells. The results of the Annexin V/PI staining indicated that BtxA induced apoptosis after 24 hours. The 1.45U, 1.75U, and 1.65U of BtxA respectively induced more than 50% apoptosis in MCF 7, SK-OV-3, and CHO cell lines. The results of caspase 3 showed more protein expression in the treated group compares to the control group. Conclusion: BtxA, as a neurotoxin, can insert therapeutic anti-cancer and apoptotic effects on various types of cancerous cells; further studies need to illuminate the possible mechanisms.